Optimization of Extraction of Natural Dye from Turmeric - Tengku Khamanur Azma, Tg. Mohd Zamri; Mimi Sakinah, A. M.; Zularisam, A. W. (Universiti Malaysia Pahang, 2016)
Nowadays, natural dyes plays an important role in the textile industry because the needs of replacement synthetic dyes which have a lots of conflict with the environmental issues. This means that the development of natural dyes will give benefits to all sides because users friendly for dyeing industry. The study seeks to explore and capture some natural plants from which dyes can be extracted. The scope is to optimize the extraction of each colour natural dyes from the natural sources. Determination of optimum parameters for extraction of natural dye are temperature, solid liquid ratio and time with one factor at one time (OFAT) followed with an optimization by response surface method (RSM) by utilizing Design Expert V8.0.6. In this research, turmeric will be used as the source of natural dye. The pigment that is contained in turmeric called curcumin. The absorption of curcumin increases with increase of extraction temperature and reaches a maximum value at 60 °C. The extraction time for curcumin reached equilibrium at minutes 25 while the solid liquid ratio on extraction of turmeric found to be 1:10 then it reached equilibrium